IDENTIFICATION OF HYDROLOGICAL PERIODS BY MEANS OF DESCRIPTIVE STATISTICS AND NON PARAMETRIC TESTS OF PETTITT AND MANN-KENNDALL - Barbosa Sousa, Rodrigo Vitor [UNESP]; Rocha, Paulo Cesar [UNESP] (Univ Federal Ceara, Programa Pos-graduacao & Filosofia, 2015)
The aim of this paper is to compare results of hydrological periods obtained through different methodologies. So, descriptive statistic techniques as central trend measures: mean, dispersive measures: standard deviation (SD) and variation coefficient (CV), selected with base in the Indicators of Hydrologic Alteration (IHA) are utilized. Additionally, trend curves obtained through linear regression are used. Subsequently, the non- parametrical techniques of Pettitt and ManKendall are used for to compare the results. The analyses are based in mean, maximum and minimum interannual discharge time series with period of 78 years. The data are of the fluviometric stations of Jataizinho - 64507000 and Tibagi - 64465000, localized in the Tibagi River, Paran State, Brazil. The results show two hydrological periods and discharges with upward trend and also point that the techniques used are compatibles.
Keywords: Hydrology; Discharge; Variability; Statistic